Coping with creative destruction: Reducing the costs of firm exit - Andrews, Dan; Saia, Alessandro (Paris, 2017)
"A policy framework that does not unduly inhibit the creative destruction process is vital to sustaining productivity growth. Yet, a key question is what happens to workers who lose their jobs due to this process and what are the policies that minimise the costs of worker displacement? Accordingly, this paper exploits a retrospective panel of workers in 13 European countries over the period 1986-2008 to explore the factors which shape the re-employment prospects of workers displaced due to firm exit. The results suggest that higher spending on active labour market policies (ALMPs), financed through an offsetting reduction in spending on passive measures, can aid the re-employment prospects of displaced workers. There may also be a case to better tailor ALMPs to workers displaced by firm exit to the extent that the re-employment probabilities of this group of workers are more sensitive to ALMPs than workers that are displaced for other involuntary reasons. The effectiveness of ALMPs is also enhanced by lower entry barriers in product markets and higher public sector efficiency, while reductions in the labour tax wedge can aid the re-employment prospects of displaced workers. Finally, regional mobility emerges as a key channel through which workers who lose their job due to plant closure become re-employed, suggesting that housing market policies may also be relevant."